Currency Orders and Exchange Rate Dynamics: An Explanation for the Predictive Success of Technical Analysis - Osler, Carol L. (Journal of Finance, 2003)
Abstract This paper documents clustering in currency stop‐loss and take‐profit orders, and uses that clustering to provide an explanation for two familiar predictions from technical analysis: (1) trends tend to reverse course at predictable support and resistance levels, and (2) trends tend to be unusually rapid after rates cross such levels. The data are the first available on individual currency stop‐loss and take‐profit orders. Take‐profit orders cluster particularly strongly at round numbers, which could explain the first prediction. Stop‐loss orders cluster strongly just beyond round numbers, which could explain the second prediction.